Penyuluhan Anti Korupsi Bagi Taruna Untuk Menyiapkan Generasi Emas 2045 - Muhammad Ali Ulat; Handayani Handayani; Muhfizar Muhfizar; Sigit Purnomo Sidhi; Mustasim Mustasim; Hendra Poltak (Politeknik Kelautan dan Perikanan Sorong, 2021)
Anti-corruption values ​​need to be crystallized to cadets as provisions in welcoming the golden generation towards an advanced and civilized nation. These values ​​become culture and strengthen superior character which can be a provision in community activities and work activities. Community service activities are carried out using the online method using online meetings with the concept of screen sharing. Thirty-two target partners attended two material sessions.